Quantifying the Contribution of Each Driving Force to the Lagrangian Residual Velocity in Xiangshan Bay - Deng, Fangjing; Jiang, Wensheng; Zong, Xiaolong; Chen, Zhaoyun (Frontiers in Marine Science, 2022)
A three-dimensional numerical model is used to quantitatively evaluate the contribution of each driving force to the Lagrangian residual velocity (LRV) in Xiangshan Bay under conditions of constant buoyancy gradient in time and multi-frequency tide. Each component of the LRV from various processes is derived by tracking each driving force in a tidal period along the particle trajectory. For a comparison of the results, the driving force in the momentum equations is averaged at the fixed points to obtain six components of the Eulerian residual velocity (ERV). A quantitative evaluation of the contribution of each component to the total ERV and total LRV is performed. The sum of the acceleration component, nonlinear advection component, and barotropic pressure gradient component of ERV determines the structure of the total ERV. The LRV is influenced by different dynamic mechanisms. The barotropic pressure gradient component of LRV determines the outflow pattern of the total longitudinal LRV at the surface of the inner Xiangshan Bay, and the density gradient component of LRV is the main determinant of the structure of the total longitudinal LRV at the bottom of the inner Xiangshan Bay. The eddy viscosity component causes the total longitudinal LRV to flow seaward in the Niubi Channel. The sum of the acceleration component and nonlinear advection component of LRV is the main contributor to the inward total longitudinal LRV in the Fodu Channel. The barotropic pressure gradient component leads to total lateral flow in the outer Xiangshan Bay. The collective effect of the components induced by all of the forces determines the structure of the lateral LRV in the inner Xiangshan Bay.